Blazars as Ideal Reference Frame Objects - Sargent, A. (2025)
Despite achieving sub-milliarcsecond per-source position accuracies and an overall celestial reference frame (CRF) stability of a few tens of micro arcseconds, consistent source positions and frame orientations across wave lengths has not yet been achieved, hampering the goal of producing a wave length-independent CRF. Source position discrepancies are seen both between radio frequencies (e.g., X and K) and between the radio and the optical CRFs (i.e., ICRF3 and Gaia-CRF3), with about 15% of ICRF3 sources having statistically significant optical-radio position offsets. It has recently been shown by the U.S. Naval Observatory that the prevalence of optical-radio position offsets is inversely correlated with photometric variability, strongly indicating blazars as astrometrically stable sources. In this presentation, I review important recent results on the relationship between blazars and multi-wavelength astrometric stability and argue that blazars should be the object of choice for the next ICRF and future geodetic observations.